Autologous Serum Skin Test in Chronic Idiopathic Urticaria - Pokhrel, Kumar; Subedi, S.; Acharya, S. (Journal of Nepalgunj Medical College, 2016)
Background: Urticaria is a short-lived swelling of skin and mucosa due to plasma leakage by immune and non immune mediated activation and released of mediators from mast cell and basophil. Autoimmune urticaria tends to have a high itch and wheal score than other type of urticaria. Its diagnosis is practically relied upon clinical suspicion and autologous serum skin test. Autologous serum skin test (ASST) is the simple and cost effective test to differentiate autoimmune urticaria from the bulk of chronic urticaria patients. Objective: To compare the features of chronic urticaria in patients having positive versus negative autologous serum skin test (ASST).Materials and methods: Cross-sectional hospital based study was conducted among 90 chronic urticaria patients (CIU) attending the outpatient dermatology department of Nepalgunj Medical College, Nepalgunj, during one year period. The study was conducted after ethical approval from the institutional committee. The patients were diagnosed on the basis of the appearance of continuous or recurrent hives with or without angioedema for more than 6 weeks. Patients who suffered from either acute urticaria or urticarial vasculitis or physical urticaria or other systemic diseases known to cause urticaria were excluded. Standard tools and techniques were used to prepare antilogous serum and injection of the serum and interpretation of the result. The test result was Interpreted as positive and negative autologous serum skin test.Results: ASST was positive in 42% of the patients and negative in 58% of the patients. The ASST-positive patients had a higher mean urticaria activity score and median duration of wheals in comparison with the ASST-negative patients. Wheals lasted for significantly longer duration in patients with positive ASST. Patients with positive ASST had more frequent attacks which was statistically significant compared to the ASST-negative group. The mean urticaria activity score was significantly higher in the ASST-positive patients than that in the ASST-negative patients.Conclusions: Autologous serum skin test may be a useful screening test for autoimmune urticaria and may be used as a simple and cost-effective test for the classification of chronic urticaria.JNGMC Vol. 12 No. 2 December 2014, page: 6-10